Desiccation increases the hatching of resting eggs of a freshwater calanoid copepod. (21st February 2022) - Brazil, Thamires; Caetano, Ana Clara L; Vargas, Anderson L; Bozelli, Reinaldo L; Santangelo, Jayme M
Abstract: Many former permanent aquatic habitats now face occasional desiccation due to human activities. Zooplankton might recover from droughts after the hatching of resting eggs, but how desiccation duration affects the viability and hatching patterns of resting eggs is unclear. This study evaluated how desiccation of varying durations (0, 3, 6 and 9 months) affects the hatchling numbers of the freshwater calanoid Notodiaptomus iheringi inhabiting a permanent lake . Hatchlings were observed across all desiccation treatments, and hatchling abundance was higher in longer desiccation treatments. Resting eggs of N. iheringi survive desiccation for up to 9 months even though the tested population originated from sediments of a permanent lake. Desiccation may stimulate hatching by terminating dormancy and by weakening (wet) sediment adversity. Knowledge of the hatching patterns of resting eggs of varying taxa after desiccation can help to understand how zooplankton communities recover after droughts.